THE IMPLEMENTATION OF GREEN MARKETING IN INDONESIA - Rahayu Lestari; Resti Hardini; Melati; Kumba Digdowiseiso; ha Rofusila Abu Hasan (RADJA PUBLIKA, 2024)
The purpose of this extensive literature review on the application of green marketing in Indonesia is to assess the advancements and difficulties associated with implementing sustainable marketing techniques. The background of the research emphasizes how companies are being encouraged to engage in environmentally friendly business practices and how environmental issues are becoming more widely known. Through the systematic identification and analysis of literature pertaining to the application of green marketing in Indonesia, the research methodology employs a Systematic Literature Review (SLR) approach. The study's findings show encouraging advancements in environmentally friendly business practices, such as modifications to supply chains and a focus on environmental values in advertising campaigns. Notwithstanding, certain obstacles persist, such as disparities in consumer comprehension and challenges in executing sustainable business strategies. The keys to success were found to be government and policy initiatives that support sustainability as well as business initiatives to raise consumer awareness. The research's discussion emphasizes Indonesia's potential for a constructive change in the direction of a more ethical and sustainable corporate culture. In summary, Indonesia's adoption of green marketing initiatives is indicative of a promising trend toward more ecologically friendly corporate practices. To overcome current obstacles and promote future advancements in Indonesia's adoption of green marketing, the government's assistance and consumer education are essential.